Cincinnati : a chronological & documentary history, 1676-1970 - Vexler, Robert I. (Dobbs Ferry, N.Y. : Oceana Publications, 1975)
A chronology of the development of Cincinnati including pertinent documents and a bibliography.
Bibliography: p. 139-150.
Keywords: Cincinnati (Ohio) -- History -- Chronology; Cincinnati (Ohio) -- History -- Sources